MORPHOLOGICAL STRUCTURE OF THE HEPATIC-PANCREATIC AMPULLA OF RABBITS (Journal of Universal Science Research, 2024)
Gastrohepatoduodenal system is the most complex in structure and important in functional significance department of the digestive tract. It is here that the secretion of the main digestive juices into the intestinal cavity takes place, and this process is strictly coordinated and depends on the ingestion of chyme into the intestinal cavity. Consequently, the secretion of bile and pancreatic juice into the intestine depends on the digestive activity of the duodenum. The production of bile by the liver is a continuous process, and when there is no need of bile in the body, it accumulates in the gall bladder and is secreted into the duodenum at the time of digestion.